Report of the Fourth Russell Tribunal on the rights of the Indians of the Americas = . Informe del Cuarto Tribunal Russell sobre los derechos de los pueblos indigenas de las Americas (Werkgroep Inheemse Volken, 1980)
1. Conclusions [corr.ed.]